2021
DOI: 10.3390/cells10113014
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Designing of a Multitope Vaccine against Rhizopus microsporus with Potential Activity against Other Mucormycosis Causing Fungi

Abstract: During the current era of the COVID-19 pandemic, the dissemination of Mucorales has been reported globally, with elevated rates of infection in India, and because of the high rate of mortality and morbidity, designing an effective vaccine against mucormycosis is a major health priority, especially for immunocompromised patients. In the current study, we studied shared Mucorales proteins, which have been reported as virulence factors, and after analysis of several virulent proteins for their antigenicity and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 92 publications
2
16
0
Order By: Relevance
“…Molecular dynamics simulation was perused for evaluating the relative epitope-TLR motions, conformation-time evolution, and thermodynamic stability under near-physiological conditions (51). Using GROMACS-5.1.4 and CHARMM36m forcefield, the constructed models of the multiepitope vaccine in complex with either TLR-4 or TLR-8 were individually simulated through 100 nsall atom molecular dynamics as previously reported (24,52). Protein complexes were solvated within TIP3P water and under periodic boundary conditions keeping the protein complex at 10 Å marginal distances from the box margins.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics simulation was perused for evaluating the relative epitope-TLR motions, conformation-time evolution, and thermodynamic stability under near-physiological conditions (51). Using GROMACS-5.1.4 and CHARMM36m forcefield, the constructed models of the multiepitope vaccine in complex with either TLR-4 or TLR-8 were individually simulated through 100 nsall atom molecular dynamics as previously reported (24,52). Protein complexes were solvated within TIP3P water and under periodic boundary conditions keeping the protein complex at 10 Å marginal distances from the box margins.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…More recently, a new field that studies the immunological data and the tools that were developed to handle these data has been named immunoinformatics (19). This novel approach was applied to develop a vaccine construct against many pathogens, starting from bacteria such as Moraxella catarrhalis (20) and Escherichia coli (21) to viruses such as Nipah virus (22) and fungi such as Candida auris (23) and Mucormycosis causing fungi (24).…”
Section: Introductionmentioning
confidence: 99%
“…These convergence and stability findings were consistent with reported studies investigating small molecule’s affinity to the SARS-CoV-2 M pro target through molecular docking and dynamics simulations. The depicted PAD and X77-related RMSD tones were as steady as those for investigated top-active anti-M pro beta-blocker agents, angiotensin II receptor blockers, marine polyketides, scalarane sesterterpenes, and natural flavonoid aglycones [ 60 , 61 , 67 , 68 , 69 ]. The latter confirmed the thermodynamic stability of PAD at the M pro pocket.…”
Section: Resultsmentioning
confidence: 84%
“…They showed that, Dedicated Outdoor Air System model reduced the CO 2 emissions to 691 tons, with a potential of reducing heating, ventilation, and air conditioning and whole-building energy use by 37% and 16%, respectively in the hot arid climate, with a return on investment of about 6% [ 76 ]. Another recent study by Soltan et al, demonstrated the first ever developed multitope vaccine against Mucormycosis causing fungi based on the immunoinformatic approach [ 77 ]. Thus, proper precautions and care in patient health and maintenance of hygienic and controlled environment are necessary to manage Mucormycosis effectively.…”
Section: Precautions and Care To Manage Mucormycosismentioning
confidence: 99%